Respuesta :

Answer:

10. x = 3 ± 2√6

11. x = 4 ± √6

12. [tex]x = \frac{- 7 + \sqrt{109}}{10}[/tex] and [tex]x = \frac{- 7 - \sqrt{109}}{10}[/tex]

Step-by-step explanation:

10. Given the quadratic equation (x - 3)² + 14 = 38

We have to solve it by square root.

Now, (x - 3)² + 14 = 38

⇒ (x - 3)² = 38 - 14 = 24

⇒ (x - 3)² = (2√6)²

Now, square rooting both sides we get,

(x - 3) = ± 2√6

x = 3 ± 2√6 (Answer)

11. Given the quadratic equation x² - 8x + 10 = 0

We have to solve it by completing the square.

Now, x² - 8x + 10 = 0

⇒ x² - 2(4)(x) + 4² = 4² - 10

⇒ (x - 4)² = (√6)²

Now, square rooting both sides we get,

x - 4 = ± √6

x = 4 ± √6 (Answer)

12. Given the quadratic equation 5x² + 7x - 3 = 0

We have to solve it by quadratic formula.

Hence,

[tex]x = \frac{- 7 + \sqrt{7^{2} - 4 (5)(- 3)}}{2(5)}[/tex] and [tex]x = \frac{- 7 - \sqrt{7^{2} - 4 (5)(- 3)}}{2(5)}[/tex]

[tex]x = \frac{- 7 + \sqrt{109}}{10}[/tex] and [tex]x = \frac{- 7 - \sqrt{109}}{10}[/tex] (Answer)

ACCESS MORE